Reversible electrical percolation in a stretchable and self-healable silver-gradient nanocomposite bilayer - Jinhong Park; Duhwan Seong; Yong Jun Park; Sang Hyeok Park; Hyunjin Jung; Yewon Kim; Hyoung Won Baac; Mikyung Shin; Seunghyun Lee; Minbaek Lee; Donghee Son (Nature Communications, 2022)
Smart healthcare devices, which interacts with the human body by recording, analyzing and processing physiological signals, need soft and biocompatible electronics. Here, Son et al. report a self-healable and stretchable resistive switching random-access memory made of a Ag-gradient nanocomposite.